What, Me Worry? Research Policy and the Open Embrace of Industry-Academic Relations - Holman, Bennett (Frontiers in Research Metrics and Analytics, 2021)
Private companies provide by far the most funding for scientific research and development. Nevertheless, relatively little attention has been paid to the dynamics of industry‐funded research by philosophers of science. This paper first provides an overview of the epistemic concerns expressed within the philosophy of science literature. Next I turn to a completely parallel literature in the field of science policy that full-throatedly promotes industry-academic collaboration. Surprisingly, this line of research is almost, if not completely, independent from the philosophical literature. After providing an overview of this literature, I focus on understanding how the science-policy field understands such collaborations and why they seem to have no reservations about such relationships and why philosophy of science is generally focussed on the drawbacks of industry funidng. I conclude by considering how the two literatures might be fruitfully integrated and the challenges that each poses for the other.